2017
DOI: 10.1364/josab.34.001478
|View full text |Cite
|
Sign up to set email alerts
|

Active plasmon injection scheme for subdiffraction imaging with imperfect negative index flat lens

Abstract: We present an active physical implementation of the recently introduced plasmon injection loss compensation scheme for Pendry's non-ideal negative index flat lens in the presence of realistic material losses and signal-dependent noise. In this active implementation, we propose to use a physically convolved external auxiliary source for signal amplification and suppression of the noise in the imaging system. In comparison with the previous passive implementations of the plasmon injection scheme for sub-diffract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 93 publications
(91 reference statements)
1
42
0
Order By: Relevance
“…It is evident that the silver lens is incapable of resolving the object shown by the black line in figure 2 Figure 2(c) shows how the losses and noise start to progressively degrade the image spectrum from k y ≈ 2k 0 , where k 0 is the free-space wavenumber. Eventually, the image spectrum is completely overwhelmed by the noise and cannot be recovered by passive deconvolution or in- creased illumination intensity since both processes proportionally amplify noise [18]. In conclusion, a selective amplification with the auxiliary must be initiated from k y ≈ 2k 0 and progressively moved to higher spatial frequencies.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It is evident that the silver lens is incapable of resolving the object shown by the black line in figure 2 Figure 2(c) shows how the losses and noise start to progressively degrade the image spectrum from k y ≈ 2k 0 , where k 0 is the free-space wavenumber. Eventually, the image spectrum is completely overwhelmed by the noise and cannot be recovered by passive deconvolution or in- creased illumination intensity since both processes proportionally amplify noise [18]. In conclusion, a selective amplification with the auxiliary must be initiated from k y ≈ 2k 0 and progressively moved to higher spatial frequencies.…”
mentioning
confidence: 98%
“…Hence, the selective amplification process can be applied till k y = 7k 0 . One important reason for the failure of the numerically calculated transfer function is the finite spatial extent of the image and object planes which introduces errors in the Fourier transform calculations as discussed in [18].…”
mentioning
confidence: 99%
“…To push the performance of our compensation method further, we developed an active version which relies on the coherent convolution of a high spatial frequency function with an object field focused by a lossy NIFL. 52 Selective amplification of a small band of spatial frequencies by spatially filtering the object under a strong illumination beam can favorably alter the transfer function so that spatial frequency components which would originally be lost to noise can be successfully transferred to the image plane. In this article, we present a more advanced and versatile method that alternatively employs a simple plasmonic superlens structure illuminated by incoherent UV light, avoiding the complexity and practical difficulties related to phase retrieval or phase detection of coherent fields.…”
mentioning
confidence: 99%
“…In conclusion, we have proposed a near-field spatial filter for the active implementation [23] of the recently introduced Π loss compensation scheme [18]. The "tunability" and "selective amplification" characteristics of the auxiliary source in [23] can be realized with layered metal-dielectric systems with hyperbolic dispersion. We have demonstrated that the convolution, which is vital for the construction of the auxiliary source, can be achieved in the layered system.…”
Section: Discussionmentioning
confidence: 99%
“…In [23], the auxiliary source is defined as the convolution of the object field with a function whose Fourier transform, P (k y ) = F {P (y)}, is a Gaussian. In the reciprocal space, the product of the object spectrum with this Gaussian represents the amplification provided to a band of Fourier components.…”
Section: Theorymentioning
confidence: 99%